2021
DOI: 10.3389/fphar.2021.680585
|View full text |Cite
|
Sign up to set email alerts
|

Xanthohumol Attenuated Inflammation and ECM Degradation by Mediating HO-1/C/EBPβ Pathway in Osteoarthritis Chondrocytes

Abstract: Osteoarthritis (OA) is the most frequent and disabling disease in developed countries. The progressive degeneration of articular cartilage characterized as thinner and erosive. Inflammation is well-known to be involved in OA development. However, there are no effective therapeutic strategies to cure it. Xanthohumol (XH) is a natural prenylflavonoid isolated from hops and beer. The protective activity of XH against OA chondrocytes inflammation and ECM degradation is unclear. In this article, we found that XH si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Doses of xanthohumol used in the present study were based on those found in ~ 500 ml beer after wort boiling, where most of the xanthohumol is isomerized to isoxanthohumol [31]. Despite using markedly lower doses than other studies showing anti-inflammatory effects in rodents [20,32,33], in the present study, xanthohumol was detected in plasma after the ingestion of the xanthohumol containing drink and LTA-dependent activation of PBMCs was markedly lower after the ingesting of the xanthohumol containing beverage than the placebo. However, due to the variability between subjects cytokine levels between the placebo and xanthohumol group did not differ significantly when compared to each other.…”
Section: Discussionmentioning
confidence: 99%
“…Doses of xanthohumol used in the present study were based on those found in ~ 500 ml beer after wort boiling, where most of the xanthohumol is isomerized to isoxanthohumol [31]. Despite using markedly lower doses than other studies showing anti-inflammatory effects in rodents [20,32,33], in the present study, xanthohumol was detected in plasma after the ingestion of the xanthohumol containing drink and LTA-dependent activation of PBMCs was markedly lower after the ingesting of the xanthohumol containing beverage than the placebo. However, due to the variability between subjects cytokine levels between the placebo and xanthohumol group did not differ significantly when compared to each other.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed, that XN predominantly binds to the monocyte/ macrophage fraction of PBMCs, while no binding to T- and B-cells were shown in these experiments [ 14 ]. Furthermore, while using lower doses than other groups when showing anti-inflammatory effects in mice and rats [ 11 , 24 , 25 ], in the present study, LPS-dependent activation of PBMCs was dampened by XN derived through a XN-rich hop extract when compared to the placebo. These results are in line with recent findings of our own group showing that and oral intake of XN in doses alike can diminish the LTA-dependent immune responses of PBMCs in humans [ 14 ].…”
Section: Discussionmentioning
confidence: 44%
“…In addition, the activation of inflammatory signaling pathways such as MAPK or NF-κB or the release of a large number of pro-inflammatory cytokines (iNOS, COX-2, TNF-α, IL-6, and IL-1β) can trigger the imbalance of anabolism and catabolism in chondrocytes, leading to the occurrence of cartilage degeneration and presence of clinical symptoms of OA such as pain and swelling ( 26 28 ). Basic experimental studies have shown that measures to inhibit inflammatory responses can restore the balance of anabolism and catabolism in chondrocytes and alleviate cartilage damage ( 29 ). Besides, clinical evidence has confirmed that the administration of non-steroidal anti-inflammatory drugs can effectively relieve clinical symptoms in patients with OA ( 30 ).…”
Section: Discussionmentioning
confidence: 99%